PENGARUH KEBAKARAN LAHAN TERHADAP PEREKONOMIAN MASYARAKAT DI DESA PEMATANG BOTAM, KECAMATAN RIMBA MELINTANG, KABUPATEN ROKAN HILIR - Martini "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is doing at Pematang Botam, village at Rimba Melintang subdistrict Rokan Hilir district. The purpose of this research to know about influence of land fire for income and expenditure society of Pematang Botam village Rimba Melintang subdistrict. Focus of topic this research is about income and expenditure the farmers and farm woekers. Data analysis in this research is using quantitative descriptive method. Afterthet about formulation of problems in this research are (1) How about influence of land fire for income thr farmers at Pematang Botam village?. (2) How about influence of land fire for expenditure thr farmers at Pematang Botam villege?. Data collection technique in this research is questionnaire. The samples in this research are quantity about 68 peoples that determined by slovin formula. Data analysis teaching in this research give explanation that land fire happen at Pematang Botam village Rimba Melintang subdistrict to have influence an income and expenditure thr farmers also farm woekers. Disadvantage that experienced society caused land fire was very influenced their life sustainability disadvantage of economy caused land fire felt by every society. There are impact of it: (1)healty impact, (2)Education impact, and (3)Lost of income impact. In the farmers’s income, any income concept, that are (1)Income of salary and wage, (2)Income of productive assets, and (3)Income of government. Whereas in expenditure to be found that influenced haousehold food’s expenditure, that are (1)Haosehold income, (2)Education level of haousewife, (3)Quantity of family members, and (4)Quantity of thr raskin rice that they get.    Keywords: Influence, Land Fire, Income, Expenditure